2021
DOI: 10.1177/13548166211037406
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hurricane strikes on cruise ship and airplane tourist arrivals in the Caribbean

Abstract: We investigate the impact of hurricanes on airplane and cruise ship arrivals in the Caribbean. To this end, we construct a monthly panel of airline and cruise ship arrivals and hurricane destruction and employ a panel vector autoregressive model with an exogenous shock (VARX) to quantify the dynamic effects of tourist arrivals after a hurricane for 18 Caribbean countries over the period 2000–2013. The results suggest an immediate decline in the month of a strike and up to one month after on cruise ship (2.33 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The increased incidence of typhoons or tropical storms due to climate change in coastal destinations obviously puts tourists at risk. Research has shown that cruise ships and airplanes were both negatively affected by the incidence of hurricanes at popular tourist destinations, such as the Caribbean and the Canary Islands (Carballo Chanfón et al , 2021; Yanes Luque et al , 2021). In addition, changes in climate, for instance increased temperature, may also result in conditions like intense heat waves that reduce comfort for tourists (Matzarakis et al , 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The increased incidence of typhoons or tropical storms due to climate change in coastal destinations obviously puts tourists at risk. Research has shown that cruise ships and airplanes were both negatively affected by the incidence of hurricanes at popular tourist destinations, such as the Caribbean and the Canary Islands (Carballo Chanfón et al , 2021; Yanes Luque et al , 2021). In addition, changes in climate, for instance increased temperature, may also result in conditions like intense heat waves that reduce comfort for tourists (Matzarakis et al , 2013).…”
Section: Resultsmentioning
confidence: 99%
“…For destinations devastated by natural disasters, the most striking feature is generally a decrease in tourist arrivals [34][35][36]. Tourists generally prefer to travel with their close family or friends after a natural disaster [37], and their perception of risk varies according to socio-demographic characteristics such as age, gender, and education [38]. In addition, tourists' familiarity with the destination also influences their perception of risk, which in turn affects their travel needs and decisions.…”
Section: The Impact Of Crisis Events On Tourism Demandmentioning
confidence: 99%
“…Several recent studies explore the implications of this damage to various aspects of economic activity. This includes Caribbean hurricanes' impacts on incomes and GDP (e.g., Strobl, 2012;and Campbell and Spencer, 2021) on proxies for GDP such as nightlights (Bertinelli and Strobl, 2013;; their historical impact on trade, particularly sugar trade, and trade flows more generally (Mohan and Strobl, 2013;Mohan, 2023;Bensassi et al, 2017); their impact on households' incomes and asset holdings (Jakobsen, 2012;Henry et al, 2020); their impact on important economic sectors such as agriculture (Mohan, 2017;Gassebner et al, 2010;Spencer and Polachek, 2015;Mohan and Strobl, 2017), and tourism (Carballo et al, 2023); their impact on financial indicators such as international reserves , prices (Heinen et al, 2019), and banking sector stability (Brei et al, 2019); and their effect on fiscal accounts (Ouattara et al, 2018;Mohan and Strobl, 2021). Nevertheless, Mohan et al (2018) report that there is significant heterogeneity in the impact of storms on some of the various macroeconomic aggregates identified above, even within the relatively narrow context of the Caribbean Island countries.…”
Section: Introductionmentioning
confidence: 99%